THE WAYS OF QUALIFICATIONS FRAMEWORK DEVELOPMENT: THE TEMPUS PROJECT EXPERIENCE - Dmitry V. Kharitonov (Russian State Vocational Pedagogical University, 2015)
The consortium of Russian and European universities carried out the project of Qualifications Framework Development for Higher Educational Institutions in the Ural region in 2009-2010, which consistently resolved a new task of creating the professional and educational environment in the Ural Federal Region, and developed the proposals for the national qualifications framework elaboration. The project involved studying the European experience and academic staff surveys, developing the qualification grid for educational institutions and industrial enterprises with different forms of ownership, and finally - creating and approbating the Regional Qualifications Framework adapted to the Russian realities. As a result, the research outcomes were incorporated both in the Ural State Federal University qualifications framework in metallurgy, and the new Federal State Educational Standard.